Nilai-Nilai Maqasid Syariah dalam Fungsi Keluarga di Tengah Pandemi Covid-19 - Apik Anitasari Intan Saputri; Athoillah Islamy (Institut Agama Islam Negeri Kerinci, 2021)
This study intends to explore strategies for inculcating maqasid shariah values ​​in family functions in the midst of the Covid 19 pandemic. This qualitative research is in the form of a literature study. This type of research is a conceptual research with a philosophical normative approach. The analytical theory used is the contemporary maqasid shariah theory which was coined by Jasser Auda. The results of the study show that efforts to instill maqasid shariah values ​​in responding to the Covid-19 pandemic can be manifested in various family functions. First, objectification of the value of hifz din and hifz 'aql in religious functions in the form of inculcating the values ​​of faith and tawakkal accompanied by a rationality basis of reason based on science (science). Second, the objectification of the value of the hifz nafs in socio-cultural and loving functions in the form of habituation of a clean lifestyle and upholding mutual love. Third, the objectification of the value of the hifz nasl in reproductive function is in the form of an emphasis on maintaining the immune system by consuming various types of food that are full of nutrition, nutrition, and also do not forget to exercise regularly. Fourth, the objectification of the value of hifz maal in the economic function is the cultivation of an iqtisad (frugal) lifestyle.